16p11.2 deletion is associated with hyperactivation of human iPSC-derived dopaminergic neuron networks and is rescued by RHOA inhibition in vitro - Maria Sundberg; Hannah Pinson; Richard S. Smith; Kellen D. Winden; Pooja Venugopal; Derek J. C. Tai; James F. Gusella; Michael E. Talkowski; Christopher A. Walsh; Max Tegmark; Mustafa Sahin (Nature Communications, 2021)
16p11.2 CNVs are associated with neurodevelopmental disorders. Here, the authors show that 16p11.2 deletion is associated with hyperactivation of human iPSC-derived dopaminergic neuron networks and is rescued by RHOA inhibition in vitro.